Historical "intimacy" in Malay urban core configurations - a comparative analysis - Ibrahim, Illyani; Abdul Latip, Nurul Syala; Jahn Kassim, Puteri Shireen; Harun, Nor Zalina (2018)
This paper focuses on analysis of the historical pre-colonial configurations of a series of urban cores in Malay sites along the Selat Melaka. The objective of this research is to identify the pattern and variations of each pre-colonial royal town from the perspective of urban design principle such as "intimacy" and "walkability" which can affect and reduce, long-term sustainable parameters in tropical cities such as ‘urban heat island'. While this traditional character is increasingly disappearing due to modern urbanization, the difficulty is related to the degree of organic character or randomness in the past layout of these traditional urban cores. It argues that such configurations reflects to a degree of ‘intimacy’ which was ruptured during Colonial eras. The main finding is Malay royal town does obey the urban design principle of an ‘intimacy’ and ‘walkability’. The ‘intimacy index’ for historical Malay city are as follow; distance from palace to; Masjid (160 meter), Padang/open spaces (120 meter), settlement (300 meter), market (220 meter) and aristocrat houses (60 meter). This finding can be used as a guidelines for the preparation of the developing the future city.